Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1090/s0002-9939-2014-11998-8
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of surfaces containing an elliptic quartic curve

Abstract: A very general surface of degree at least four in P 3 contains no curves other than intersections with surfaces. We find a formula for the degree of the locus of surfaces in P 3 of degree at least five which contain some elliptic quartic curves. We also compute the degree of the locus of quartic surfaces containing an elliptic quartic curve, a case not covered by that formula.so F 4 contains the pencil of elliptic quartics A 1 − tQ 2 , A 2 + tQ 1 , t ∈ P 1 ; setting t = ∞, we find Q 1 , Q 2 . Similarly, we get… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Avritzer & Vainsencher [34], [3] obtained an explicit description of the component W eqc of elliptic quartics of the Hilbert scheme Hilb 4t (P 3 ). This has been used in [9] for enumerating curves in cer-tain Calabi-Yau 3-folds, and in [6] for studying Noether-Lefschetz loci of systems of surfaces in P 3 . G. Gotzmann [13] has shown that Hilb 4t (P 3 ) consists of two irreducible components; the second one parameterizes unions of a plane quartic curve and a zero dimensional subcheme of P 3 of length 2.…”
Section: Surfaces Singular Along Elliptic Quartic Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…Avritzer & Vainsencher [34], [3] obtained an explicit description of the component W eqc of elliptic quartics of the Hilbert scheme Hilb 4t (P 3 ). This has been used in [9] for enumerating curves in cer-tain Calabi-Yau 3-folds, and in [6] for studying Noether-Lefschetz loci of systems of surfaces in P 3 . G. Gotzmann [13] has shown that Hilb 4t (P 3 ) consists of two irreducible components; the second one parameterizes unions of a plane quartic curve and a zero dimensional subcheme of P 3 of length 2.…”
Section: Surfaces Singular Along Elliptic Quartic Curvesmentioning
confidence: 99%
“…Pulling back E d , D d in (7) to W, we may as well simplify notation and assume W = W smooth. We now argue as in [6] and [33]. Recall D d is a direct image of a sheaf over W × P n (cf.…”
Section: Introductionmentioning
confidence: 99%
“…See a script for the production of random examples in [21]. Just as in [8], the proof of Theorem A uses Grothendieck-Riemann-Roch [13, 15.2, p. 286] to show the polynomial nature and bound the degree of q W (d).…”
Section: Introductionmentioning
confidence: 99%
“…Asking surfaces of a given degree to contain say, a (few) line(s), or a conic, a twisted cubic, etc., defines subvarieties, the so called Noether-Lefschetz loci, in the appropriate projective space. There are polynomial formulas for their degrees, [4], [14].…”
Section: Introductionmentioning
confidence: 99%
“…An argument employing Grothendieck-Riemann-Roch (cf. [4]) shows that there is a formula for the degree of W d ⊂ PF d as a polynomial in d. Actually we got by interpolation the following polynomial of degree 54 (cf. [16] for a script):…”
mentioning
confidence: 99%